Artifact for Enhancing Genetic Improvement of Software with Regression Test Selection - Guizzo, Giovani; Petke, Justyna; Sarro, Federica; Harman, Mark (2021 IEEE/ACM 43rd International Conference on Software Engineering: Companion Proceedings (ICSE-Companion), 2021)
We present in this document the basic information needed to download, unpack, and then interpret the instructions we provide as requested in the ICSE 2021 Artifact Submission Guidelines. The artifact contains all the subject programs, scripts, tools, results, and a series of guidelines on how to use them. We aim at obtaining the badges of Available and Reusable. In order to do so, we have added all the components needed for the full execution of the experiments and analyses as we originally did during the writing of our paper, making it readily available. Furthermore, we have included instructions to the INSTALL file on how to add new programs to the experiments and analyses, making it reusable for the next researchers that intend to replicate or extend our experiments.